PENGARUH VARIABEL MAKROEKONOMI TERHADAP PROFITABILITAS BANK KONVENSIONAL BUKU 4 DI INDONESIA - Yusuf, Sandi Fitra; Triani, Mike (Universitas Negeri Padang, 2021)
This study explains the extent of the influence of macroeconomic variables on the profitability of BUKU 4 banks in Indonesia. The macroeconomic variables consist of economic growth (X1), inflation (X2), Bank Indonesia Interest Rate (BI Rate) (X3, and Profitability is measured by the ROA (Return) ratio. On Asset). This study combines cross section data of 7 banks with time series from 2010-2019, with the Panel Regression method with the Random Effect model selection test. The results show that: (1) Economic growth has a positive and significant effect on bank profitability. conventional BUKU 4 in Indonesia, (2) Inflation has a positive and insignificant effect on the profitability of conventional BUKU 4 banks in Indonesia, (3) the Bank Indonesia Interest Rate (BI Rate) has a positive and insignificant effect on the profitability of conventional BUKU 4 banks in Indonesia.